The ethics of resettlement: Australia and the Asia-Pacific Region. Issue 2 (17th February 2016) - O'Sullivan, Maria
Abstract : One of the key problems at the heart of refugee protection today is that there are large numbers of refugees attempting to seek asylum and insufficient political will in many asylum-host states to receive refugees in their territories. A proportion of these attempt to come to Australia to seek refuge – either by requesting a resettlement place through the auspices of the United Nations High Commissioner for Refugees, or by arriving directly in Australian territory (by boat or plane). Asylum-seekers who arrive by boat are disadvantaged and penalised under Australian law in that they are excluded from Australian territory and processed offshore in third countries. Successive Australian governments justify these measures by emphasising that resettlement is the 'proper' mode for claiming asylum which ensures protection is given to those refugees who are most in need. This raises fundamental ethical questions: are those chosen by resettlement countries such as Australia necessarily the refugees who are most in need? Is resettlement as a concept ethical? And should resettlement be utilised to prevent and penalise spontaneous arrivals attempting to seek asylum in a country?